2017
DOI: 10.1016/j.epsl.2016.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Potential earthquake precursory pattern from space: The 2015 Nepal event as seen by magnetic Swarm satellites

Abstract: A large earthquake of 7.8 magnitude occurred on 25 April 2015, 06:26 UTC, with the epicenter in Nepal. Here, taking advantage of measurements provided by the Swarm magnetic satellites, we investigate the possibility to detect some series of pre-earthquake magnetic anomalous signals, likely due to a lithosphere-atmosphere-ionosphere coupling, that can be a potential earthquake precursory pattern. Different techniques have been applied to Swarm data available during two months around earthquake occurrence. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 44 publications
11
69
0
Order By: Relevance
“…Even more, the frequencies shown in Figs. 5 and 6 show a spectrum (∼ µHz) lower than that studied by Hayakawa et al (2015), De Santis et al (2015, Contoyiannis et al (2016), Potirakis et al (2016a, b) andDe Santis et al (2017) (on the order of millihertz).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Even more, the frequencies shown in Figs. 5 and 6 show a spectrum (∼ µHz) lower than that studied by Hayakawa et al (2015), De Santis et al (2015, Contoyiannis et al (2016), Potirakis et al (2016a, b) andDe Santis et al (2017) (on the order of millihertz).…”
Section: Resultsmentioning
confidence: 74%
“…Despite this, there is a great amount of recent and rigorous research that has shown a statistical relation between magnetism and earthquakes, and thus, this effect could not be negligible in other magnetic properties, such as the Rc or the study of particle flux at Earth's ground level (Hayakawa et al, 2015;Contoyiannis et al, 2016;Potirakis et al, 2016a, b;De Santis et al, 2017;Oikonomou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study have shown that a multiparametric approach may provide an important contribution for better interpreting the actual origin of ionospheric anomalies. This contribution may be particularly valuable when ionospheric disturbances are investigated as possible indicators of impending earthquakes (e.g., [100][101][102][103][104][105][106][107][108]). Indeed, the integration of independent observations is nowadays expected to be a major improvement in short-term seismic hazard forecast.…”
Section: Resultsmentioning
confidence: 99%
“…Tohoku earthquake (2011) [8][9][10] Detection of a series of pre-earthquakes magnetic anomalies. Nepal earthquake (2015) [11] Abnormal variations in the amplitude and phase of these ELF signals when crossing regions of certain seismic activity.…”
Section: Precursor Phenomenon Earthquake (Year) Referencementioning
confidence: 99%
“…Another example is the possible detection of a series of pre-earthquakes magnetic anomalies that occurred on 25 April 2015, with epicentre in Nepal and a 7.8 magnitude. Detection was possible through the use of the Swarm magnetic satellites [11].…”
Section: Introductionmentioning
confidence: 99%